The Outcomes of Very Early Preterm Births in the Republic of Sakha (Yakutia) - Nyurguyana S. Baisheva; Natalia I. Douglas; Tatiana Y. Pavlova; Anisia I. Yakovleva; Tatiana E. Burtseva (International Journal of Biomedicine, 2016)
Protection of maternal and child health is a special health care industry. It largely determines the future of the nation. Therefore, it is an important matter of the state. This article presents an analysis of cases of very early preterm births (VEPB) and their outcomes in 2012-2014 in the Republic of Sakha (Yakutia) (RS (Y)). Retrospective analysis of the cases of VEPB and of the status of health of the babies born before 28 weeks of gestation was conducted during the research. The group at risk of VEPB consisted of women with burdened obstetric and gynecological history. The main causes of VEPB were premature amniorrhexis in pregnant women with carriage of infections and life-threatening severe pre-eclampsia. In the structure of morbidity of very preterm babies the first place among the main diseases belongs to perinatal lesion of CNS, the second place belongs to respiratory distress syndrome, and the third place to infectious and inflammatory diseases. In the structure of death, 57.1 % of fatal cases are babies with a term of gestation less than 28 weeks. The causes of mortality were respiratory distress syndrome, congenital pneumonia, and intraventricular hemorrhage.